PENGARUH MODEL PEMBELAJARAN MISSAURI MATHEMATICS PROJECT TERHADAP NILAI KALKULUS DIFERENSIAL - Aniswita Aniswita (JURNAL TARBIYAH, 2016)
Differential calculus is one of the basic matakuliah be matakuliah some other prerequisites mastery of differential calculus should be earnestly good attention by professors or Department Manager. The data showed that the value of the differential calculus students majoring in mathematics education IAIN Bukittinggi two years is low, i.e. 81.5% are below the criteria pass (50). One effort that can be done to improve the learning results of differential calculus is a learning model by applying Missouri Mathematics Project (MMP). This research investigates or no significant effects of the learning model MMP of differential calculus students majoring in mathematics education IAIN Bukittinggi FY 2015-2016. This research is a research experiment by comparing the value of classroom experiments with the control class.  The value is analyzed using t-test results show. There is a difference value of differential calculus class experiments with grade control so that it is concluded there is a significant influence of the MMP model of differential calculus students majoring in mathematics education IAIN Bukittinggi FY 2015-2016. Keywords: Missauri, Model Influences The Mathematics Project. The Value Of Differential Calculus